2020
DOI: 10.1093/ajcp/aqaa181
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Five SARS-CoV-2 Molecular Assays With Clinical Correlations

Abstract: Objectives Comparative assessments of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) molecular assays that have been operationalized through the US Food and Drug Administration’s Emergency Use Authorization process are warranted to assess real-world performance. Characteristics such as sensitivity, specificity, and false-negative rate are important to inform clinical use. Methods We compared five SARS-CoV-2 assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 17 publications
(17 reference statements)
3
62
0
Order By: Relevance
“…multiple clinical orders for testing and different methods used), a tie-breaker system was used whereby the reference result (positive or negative) was considered to be the result obtained by two of the three (Cue COVID-19, Hologic Aptima, and laboratory-developed RT-PCR) methods. This approach is similar to that used in another recent study of SARS-CoV-2 molecular methods in defining positive results by multiple methods to be the reference definition of positive ( Procop et al, 2020 ), and helps overcome the lack of a true reference method for SARS-CoV-2 RNA detection.…”
Section: Methodsmentioning
confidence: 92%
“…multiple clinical orders for testing and different methods used), a tie-breaker system was used whereby the reference result (positive or negative) was considered to be the result obtained by two of the three (Cue COVID-19, Hologic Aptima, and laboratory-developed RT-PCR) methods. This approach is similar to that used in another recent study of SARS-CoV-2 molecular methods in defining positive results by multiple methods to be the reference definition of positive ( Procop et al, 2020 ), and helps overcome the lack of a true reference method for SARS-CoV-2 RNA detection.…”
Section: Methodsmentioning
confidence: 92%
“…SARS-CoV-2 RT-PCR Ct values only indicate a semi-quantitative evaluation of genome quantity and are influenced by many factors. Among those factors, our study and others highlight the importance of the RT-PCR method used ( Dust et al, November 2020 , Procop et al, October 5, 2020 , Kasteren et al, July 2020 , Zhen et al, April 27, 2020 ). The potential patient contagiousness, evaluated in the foreground on clinical criteria and time from symptoms onset, cannot be determined on the sole RT-PCR Ct result and can also be partly estimated after inoculation in cell culture ( Walsh et al, October 10, 2020 ).…”
Section: Discussionmentioning
confidence: 64%
“…Up to day many different type of standards exist, as elaboration of an international calibration standard is only under progress yet ( Vogels et al, October 2020 ). A growing literature describes comparisons between SARS-CoV-2 RT-PCR techniques ( Dust et al, November 2020 , Procop et al, October 5, 2020 , Kasteren et al, July 2020 , Zhen et al, April 27, 2020 ), sometimes underlying discrepancies between assays. Our aim was to assess this issue in our local laboratory setting, to complete the analysis on clinical samples with quality controls and to highlight the importance of considering the RT-PCR performances when interpreting the Ct value.…”
Section: Introductionmentioning
confidence: 99%
“…results have been identified by the ID NOW manufacturer or among previous publications within the literature. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] PPA of the ID NOW varies widely in the literature from 48.0% to 94.1%. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] However, most of these studies suffered from poor study design or were conducted when the manufacturer still considered placing swabs in UTM as appropriate for sample collection (prior to April, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Of the clinical studies reported in the literature, the Abbott ID NOW has been shown to have excellent specificity (~100%) but sensitivity varies widely between studies (48.0% -94.1%). [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In addition, many of these studies suffer from poor study design such as comparing nasopharyngeal to nasal specimens, deviating from the product insert or having major delays in testing specimens on the ID NOW. Only two studies adhered to the FDA's recommendations for ID NOW testing, and both studies had a small sample size (<20 samples positive for SARS-CoV-2).…”
Section: Introduction Introductionmentioning
confidence: 99%